Pengaruh Pelatihan Terhadap Motivasi Karyawan Telkom Witel Ridar - Hendriani, Susi; Novrizal , Dedy (Basecamp Economics PubMed, 2024)
This study explores the relationship between Training (X) and Motivation (Y) of employees. Analysis using the simple linear regression method shows that there is a significant positive relationship between the training provided to employees and their level of motivation; the more intensive the training received, the higher the motivation generated. This is evidenced by a p-value lower than 0.05 on the regression coefficient, confirming the statistical significance of the relationship. The high coefficient of determination (R-squared) in this model indicates that the regression model is quite accurate in explaining the variability of motivation influenced by training. Based on these results, it is recommended that companies improve or develop training programs that better suit the needs of employees to improve motivation and performance. This study also emphasizes the importance of continuous evaluation of the effectiveness of training programs and additional support such as rewards to improve employee motivation on an ongoing basis.